PENGARUH SOSIAL MEDIA TERHADAP PERSEPSI PUBLIK DALAM PEMIIHAN KEPALA DAERAH DI SUMBAWA TAHUN 2020 - Irawansyah Parera; Supriadi Supriadi; Kikis Kayasi (Jurnal Studi Ilmu Pemerintahan, 2022)
The purpose of this study was to determine the impact of social media on public perception of regional head elections in Sumbawa in 2020. The method used was a qualitative method with a descriptive approach, data collection techniques with interviews, documentation, and literature studies related to the problems studied. The results of this study indicate that social media can influence public perception in the election by becoming a political campaign and marketing tool, namely the first 4Ps are products; The most important product of a political party is of course the candidate himself along with the party platform, concept, and work program of the political party itself. Second promotion: A good promotion is not luck, but a good promotion must be placed precisely where the sale will take place, how the promotion will run and for whom the promotion is. Third price: Price or price in political marketing includes several things ranging from economic, psychological image to national image. Fourth place: places related to pairs of candidates can maximize all potential voters well or effectively, political socialization to pairs of candidates can accommodate all levels of society. Candidate pairs are always able to classify, map, and analyze layers and forms of community characteristics.